2021
DOI: 10.1101/2021.11.22.21266721
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simulating the impact of vaccination rates on the initial stages of a COVID-19 outbreak in New Zealand (Aotearoa) with a stochastic model

Abstract: AimThe August 2021 COVID-19 outbreak in Auckland has caused the New Zealand government to transition from an elimination strategy to suppression, which relies heavily on high vaccination rates in the population. As restrictions are eased and as COVID-19 leaks through the Auckland boundary, there is a need to understand how different levels of vaccination will impact the initial stages of COVID-19 outbreaks that are seeded around the country.MethodA stochastic branching process model is used to simulate the ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…This suggests that separating patients by vaccination status may reduce the spread of an outbreak before diagnosis has taken place. A recently published New Zealand paper by Watson et al 16 found that despite a large number of breakthrough infections among the vaccinated, unvaccinated individuals are 3.3 times more likely to be infected and 20 times more likely to be hospitalised, hence they have a greater risk of bringing COVID-19 into hospital even if they are admitted for other reasons. 16 In terms of the implementation of separate rooms for vaccinated and unvaccinated patients, some patients and most staff did not see it as practically and/or ethically possible and thought that current practices to reduce risk were adequate.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that separating patients by vaccination status may reduce the spread of an outbreak before diagnosis has taken place. A recently published New Zealand paper by Watson et al 16 found that despite a large number of breakthrough infections among the vaccinated, unvaccinated individuals are 3.3 times more likely to be infected and 20 times more likely to be hospitalised, hence they have a greater risk of bringing COVID-19 into hospital even if they are admitted for other reasons. 16 In terms of the implementation of separate rooms for vaccinated and unvaccinated patients, some patients and most staff did not see it as practically and/or ethically possible and thought that current practices to reduce risk were adequate.…”
Section: Discussionmentioning
confidence: 99%
“…The model tracks the number of infections and the vaccination status of the infecting and infected individuals. The stochastic model used here is the same as presented in [4], which focused on the Delta variant, with the pertinent details summarized below.…”
Section: Methodsmentioning
confidence: 99%
“…15 It is unclear how testing rates will change in a highly vaccinated public; vaccinated and boosted individuals may feel less need to get tested while unvaccinated individuals may not want to get tested. Therefore, I focus purely on the impact of vaccination rates, particularly on the early stages of an outbreak when cases may be circulating undetected, and following the approach of [4], do not consider testing, contact tracing, or isolation of cases.…”
Section: Deltamentioning
confidence: 99%
See 2 more Smart Citations